Tetrahydrobiopterin Concentrations in Normal and Coronary Artery Diseased Heart Tissue - Arning, Erland; Lowes, Brian D; Taylor, Matthew RG; Meng, Xingli; Schiffmann, Raphael; Bottiglieri, Teodoro (Journal of Cardiovascular Medicine and Cardiology, 2016)
Background: Tetrahydrobiopterin (BH4) is a cofactor that plays a major role in cardiovascular health and disease. BH4 levels in the human heart have not been previously reported. Objective and Methods: Using a novel LC-MS/MS method we measured BH4 and BH2 levels in human heart tissue from subjects with (n=19) and without (n=19) coronary artery disease (CAD). Results: The concentration of BH4 was significantly lower in CAD subjects compared to controls (p=0.0006). There was a trend for a decrease in BH4/BH2 ratio (p=0.09). mRNA expression of GCH1, NOS3 and <emqdpr< em="">was not significantly different between CAD and controls.</emqdpr<> Conclusions: We conclude that the decrease in BH4 concentration in the left ventricular wall of subjects with CAD may be a causative factor or consequence of the failing heart.